Odpowiedzi

Najlepsza Odpowiedź!
2009-09-14T19:56:06+02:00
1) 10^3 * 10^8 / 10^9 = 10^11 / 10^9 = 10^2

2) 3^4 * (-3)^5 * (-3)^3 = 3^4 * (-3)^8 = 3^4 * 3^8 = 3^12

3) (-1/2)^5 * (1/2)^4 * (1/2)^6 = (1/2)^10 * (-1/2)^5 = (-1/2)^15

4) 6^2 * (-6)^7 * 6^8 / 6^14 : (-6) = 6^10 * (-6)^6 / 6^14 = 6^10 * 6^6 / 6^14 = 6^16 / 6^14 = 6^2
2009-09-14T20:05:11+02:00
1000•-10⁸:10⁹=-10³⁺⁸⁻⁹=-100
81•-3⁵•-27=3⁴⁺⁵⁺³=3¹²
-2⁻⁵•2⁻⁴•2⁻⁶=-2¹⁵
36•-6⁷•-6⁸/(6¹⁴:-6)=6²⁺⁷⁺⁸⁻¹³=6⁴
  • Użytkownik Zadane
2009-09-14T21:02:40+02:00
1) 10³ * -10⁸ / 10⁹ = -10²
2) 3⁴*(-3)⁵ *(-3)³= 3⁴⁺⁵⁺³=3¹²
3) (-2)⁻⁵ * 2⁻⁴ * 2⁻⁶=-2⁻¹⁵
4) 6² *(-6)⁷*(-6)⁸ / (6¹⁴ :-6)= -6²⁺⁷⁺⁸⁻¹³=-6⁴